Biological stress responses to multitasking and work interruptions: A randomized controlled trial - Becker, Linda; Kaltenegger, Helena C.; Nowak, Dennis; Weigl, Matthias; Rohleder, Nicolas (Psychoneuroendocrinology, 2023)
In the course of digitalization, new stressors are emerging. In modern working and living environments, two ubiquitous, technology-mediated stressors are multitasking demands and work interruptions. However, biological stress response patterns to multitasking and work interruptions have been sparsely investigated so far. We thus aimed to comprehensively assess biological stress response patterns to both stressors and, additionally, test whether responses differ between digital and partially non-digital settings. A controlled experimental set-up was established and humans’ biological markers of the Sympathetic Nervous System (SNS), the hypothalamic-pituitary adrenal (HPA) axis, and the immune system were assessed. N = 186 healthy participants (mean age: 23.2 ± 4.3 years, 74.7% female, body mass-index: 22.3 ± 3.1 kg/m2) took part in this pre-registered study. Each participant was randomly assigned to one of 6 experimental conditions (1 digital single-task, 3 dual-tasks [2 parallel tasks and 1 interruption], 1 multitasking, and 1 passive, control condition). Each one of the dual-tasking as well as the multitasking conditions included a non-digital sub-task, i.e., performing a task in presence of an examiner. All other conditions involved digital tasks only. Salivary alpha-amylase (sAA) levels as a marker for SNS reactivity significantly changed in work interruptions, parallel dual-tasking, and multitasking conditions. No changes were found for control conditions. Furthermore, no significant changes over time and no differences between the conditions were identified for three biological markers: cortisol as marker for HPA axis activity as well as for two immune system markers (secretory Immunoglobulin-A, C-reactive protein). A time course similar to sAA was found for perceived stress: with increases during task execution and decreases afterwards in multitasking and parallel dual-tasking. Yet, it did not change for the work interruption, passive control, and single-tasking condition. Overall, our findings show that dual- and multitasking are perceived as stressful and are associated with an activation of the SNS, but not with responses of HPA axis or immune system. This was consistent for digital as well as partially digital task demands. Our findings will also inform future research into the differential stress effects of digital and non-digital tasks to advance our understanding of biological stress response-patterns to multitasking and work interruptions. Therefore, our findings are highly relevant for understanding the long-term biological health effects of stress in modern (digitalized) environments.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Alpha-amylase; Cortisol; Digital stress; Multitasking; Technostress; Work interruptions